Validating temporal motion kinematics from clothing attached inertial sensors - Gleadhill, S.; James, D.; Lee, J. (Proceedings, 2018)
A major barrier to wearables utility for kinematic analysis is convenience. Attachment to skin requires significant expertise and is time consuming. Instead this research applies principles of sensor analysis to clothing attachments, to examine temporal immunity to clothing artefact. No known research has validated temporal outputs of inertial measurement units when embedded in clothing. Nine participants completed five repetitions of conventional deadlifts while being monitored with inertial sensors fixed on anatomical landmarks and embedded in clothing. The agreement of group means between timing outputs of inertial sensor anteroposterior axis data were compared between sensor locations. Will Hopkins Typical Error of the Estimate, Pearson`s correlation and a Bland Altman Limits of Agreement analysis were implemented for validation. Strong agreement was found based on trivial standardised error (<0.1) for all agreement analyses. Results support past research for applications applying temporal features of wearables to monitor human movement.